The Conditioned Environmental Center‐Periphery Hypothesis of Biogeography: Statistical Evidence From Tree Species - Pablo Antúnez; Martin Ricker (Ecology and Evolution)
ABSTRACT It has been discussed for decades whether species occur most frequently at their geographic center, and more recently at their environmental niches' center. The aim here is to analyze for each environmental gradient separately the ecological niche of 12 Mexican tree species and 16 abiotic environmental gradients, in the form of statistical probability density functions. Is a symmetrically positioned center always possible by searching for additional data? For each species‐variable combination, the occurrences along an environmental gradient were grouped in histograms. Logistic regression was used to fit a polynomial equation, whose degree depended on the number of significantly different bins. A highest‐probability interval on the gradient was determined, where 25% of the individuals were found with the highest probability. The relative distance from the center (midpoint) of the variable's range was calculated, and the feasibility of expanding the encountered interval on the environmental gradient for symmetry was analyzed. For 183 species‐variable combinations, in only 22 cases (12.0%) did the highest‐probability intervals include the midpoint of the environmental gradient. Furthermore, for 55% of the species‐variable combinations, the truncation of the environmental gradients for species makes it impossible to expand the measured range with additional data for the shorter tail. For example, precipitation cannot be negative. This truncation frequently causes asymmetry around the highest‐probability intervals. In those cases, the classical environmental center‐periphery hypothesis turns out to be wrong, whereas in the remaining cases it could apply. This has implications for biogeographical assumptions, such as where to identify the best areas for conservation or how to predict the effects of climate change. We propose a new conditioned environmental center‐periphery hypothesis: “On an environmental gradient, a given species is able to cover a certain range. For environmental gradients, where natural truncation of the environmental gradient is not limiting, the highest probability of occurrence is found away from the range's endpoints, tending towards its midpoint.”